Seasonal and height-related changes in leaf morphological and photosynthetic traits of two dipterocarp species in a dry deciduous forest in Cambodia. (1st November 2016) - Kenzo, Tanaka; Iida, Shin'ichi; Shimizu, Takanori; Tamai, Koji; Kabeya, Naoki; Shimizu, Akira; Chann, Sophal
Abstract : Background : Dry deciduous forest (DDF) is distributed throughout the monsoon area of South-east Asia. Leaf morphological and photosynthetic traits are essential for adaptation to the environmental variability and usually change with tree height and season. Aims : To clarify the differences in leaf traits as influenced by tree height, light conditions and season for two dominant dipterocarps of DDF: Dipterocarpus tuberculatus and Shorea obtusa . Methods : We measured changes in leaf traits with tree height, namely leaf mass per area (LMA), maximum photosynthetic rate ( A max ), stomatal conductance ( gs ) and nitrogen concentration (N), in the rainy and early and mid-dry seasons. To identify the effects of height and light intensity on leaf traits, we conducted multiple regression analyses using leaf traits as the dependent variables and the height, light and season as independent variables. Results : Tree height was more important for gradients in most leaf traits, especially in LMA in both species, than light intensity. Tall canopy tree leaves had greater LMA, A max and N than shorter tree leaves in the rainy and early dry seasons, although gs was almost constant. The lowest A max and gs were recorded in immature leaves, sampled in the mid-dry season, at all tree heights. Conclusions : The two dipterocarp species achieved high A max by having high gs, LMA and N in a high-light canopy environment, whereas larger, thinner leaves with low respiratory costs may contribute to efficient light capture under low-light conditions in the understorey.